Acute pulmonary embolism with arrhythmia associated with minimal change disease in adults: a case report - Rong, Chunyan; Liu, Xuhan; Wang, Baoguo; Zhang, Weihua (Frontiers in Cardiovascular Medicine, 2023)
Background Minimal change disease (MCD) is a common pathological type of nephrotic syndrome (NS), and is one of the most common causes of NS in children, but is not common in adults. MCD is sensitive to corticosteroid therapy and has a good prognosis, but is prone to relapse. Venous thromboembolism (VTE) is less common in MCD. Case presentation We report a case of acute pulmonary embolism (PE) with arrhythmia associated with MCD in adults. The hypercoagulable state caused by MCD through multiple systems may be one of the important causes of thrombosis in this patient. In addition to the conventional corticosteroid therapy, he was started on anticoagulation for VTE and PE. His hospital course was complicated by atrial tachyarrhythmias initially controlled by amiodarone but he required readmission due to recurrent atrial flutter. His clinical condition became more stable after radiofrequency ablation. Conclusion VTE associated with MCD in adults is rare. Treatment of MCD with corticosteroids may be associated with a higher risk of developing blood clots. This type of case is relatively rare and should be paid attention to. The mechanism of VTE in MCD is still a direction worthy of further research.